Different populations of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) from Central Africa are susceptible to Zika virus infection. - Basile Kamgang; Marie Vazeille; Armel Tedjou; Aurélie P Yougang; Theodel A Wilson-Bahun; Laurence Mousson; Charles S Wondji; Anna-Bella Failloux (Public Library of Science (PLoS), 2020)
Zika virus (ZIKV) is a Flavivirus (Flaviviridae) transmitted to humans mainly by the bite of an infected Aedes mosquitoes. Aedes aegypti is the primary epidemic vector of ZIKV and Ae. albopictus, the secondary one. However, the epidemiological role of both Aedes species in Central Africa where Ae. albopictus was recently introduced is poorly characterized. Field-collected strains of Ae. aegypti and Ae. albopictus from different ecological settings in Central Africa were experimentally infected with a ZIKV strain isolated in West Africa. Mosquitoes were analysed at 14- and 21-days post-exposure. Both Ae. aegypti and Ae. albopictus were able to transmit ZIKV but with higher overall transmission efficiency for Ae. aegypti (57.9%) compared to Ae. albopictus (41.5%). In addition, disseminated infection and transmission rates for both Ae. aegypti and Ae. albopictus varied significantly according to the location where they were sampled from. We conclude that both Ae. aegypti and Ae. albopictus are able to transmit ZIKV and may intervene as active Zika vectors in Central Africa. These findings could contribute to a better understanding of the epidemiological transmission of ZIKV in Central Africa and develop suitable strategy to prevent major ZIKV outbreaks in this region.